2011
DOI: 10.3892/or.2011.1380
|View full text |Cite
|
Sign up to set email alerts
|

Notch-1 activation-dependent p53 restoration contributes to resveratrol-induced apoptosis in glioblastoma cells

Abstract: Abstract. Glioblastoma is the most malignant form of adult brain tumor and is associated with a dismal prognosis. Emerging data suggest that Notch signaling participates principally in the formation and malignant progression of glioblastoma. Resveratrol is a terpenoid that exhibits broad pro-apoptotic activity in various types of cancers, including glioblastoma. However, the effects of resveratrol on Notch signaling in glioblastomas have not yet been fully elucidated. We demonstrated that resveratrol strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…In our study, it was found that resveratrol activated Notch1 signaling in the ATC context. Consistent with two other studies (36,37), this indicates that the Notch1 pathway could be another important signaling cascade involved in resveratrol-induced cell growth inhibition. In one of our previous studies, genetic induction of Notch1in the thyroid cancer xenografts profoundly suppressed tumor growth (38).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was found that resveratrol activated Notch1 signaling in the ATC context. Consistent with two other studies (36,37), this indicates that the Notch1 pathway could be another important signaling cascade involved in resveratrol-induced cell growth inhibition. In one of our previous studies, genetic induction of Notch1in the thyroid cancer xenografts profoundly suppressed tumor growth (38).…”
Section: Discussionsupporting
confidence: 92%
“…Curcumin downregulates Notch1 and induces apoptosis through inactivation of NF-κB in pancreatic cancer cells (Wang et al, 2006b) and in oral cancer cells (Liao et al, 2011). Resveratrol, a polyphenolic compound found in grapes, red wine, purple grape juice, peanuts, and some berries, induces apoptosis in part by inhibiting Notch and PI3K/AKT in T-ALL cells (Cecchinato et al, 2007) and in glioblastoma cells (Lin et al, 2011). Recently, it has been reported that resveratrol can also activate Notch2 as a mechanism of apoptosis induction in medullary thyroid cancer (Truong et al, 2011) and in carcinoid (Pinchot et al, 2011).…”
Section: Strategies To Target the Notch Signaling Pathwaymentioning
confidence: 99%
“…In addition, resveratrol was found in a high-throughput screen for the identification of Notch activating compounds using carcinoid cell lines [102], and treatment of thyroid carcinoma cells with resveratrol was shown to inhibit growth by arresting cell-cycle progression in the S-phase and induce Notch protein expression and signaling by transcriptional regulation [103, 104]. Furthermore, resveratrol also suppressed cellular growth and activated Notch expression in glioblastoma [105]. In contrast to most other studies, a microarray analysis to search for genes expressed in adipose tissue of obese men treated with resveratrol found genes of the Notch signaling pathway to be downregulated, whereas autophagy genes were found to be upregulated [106].…”
Section: When Endocytosis and Autophagy Converge At Notchmentioning
confidence: 99%